PELATIHAN BARIS-BERBARIS UNTUK GURU-GURU SMA PENJASORKES SE-JAKARTA TIMUR - iwan barata; Hartman Nugraha; Boyke Adam H Manopo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract Abstract. This study aims to create a line-up training for high school physical education teachers in East Jakarta. With the aim of research to develop the abilities and skills of the Penjasorkes high school teachers in East Jakarta. This study uses a demonstration and practice method, where the resource person gives a demonstration and is followed by direct practice by the trainees in rows. The training was conducted by 3 resource persons and 2 support team members, held at the Faculty of Sports Science, State University of Jakarta with the research subject of 20 Penjasorkes high school teachers throughout East Jakarta. From the observations made during the training, the training participants had great enthusiasm and motivation from the beginning to the end of the training. Participants are also very satisfied with this kind of training, where they can increase their knowledge, skills and expertise in marching in accordance with the TNI/POLRI's Row Regulations. Based on the results of the study, it can be concluded that the motivation and enthusiasm of the participants in participating in the marching training was very good and high. There was a positive interaction between the training implementation team and the training participants so that all training materials could be absorbed in accordance with the directions and standards. It is very important to conduct marching training for high school physical education teachers throughout East Jakarta in order to further improve the knowledge, abilities and skills of teachers so that they can maximize their abilities and expertise in marching. Abstrak Abstrak. Penelitian ini bertujuan untuk membuat pelatihan baris-berbaris untuk guru-guru SMA penjasorkes se-Jakarta Timur. Dengan tujuan penelitian untuk mengembangkan kemampuan dan keterampilan baris-berbaris para guru SMA Penjasorkes se-Jakarta Timur. Penelitian ini menggunakan metode demonstrasi dan praktek, dimana narasumber memberikan demonstrasi dan dilanjutkan dengan praktek langsung oleh peserta pelatihan baris-berbaris. Pelatihan dilakukan oleh 3 orang narasumber dan 2 orang tim pendukung, dilaksanakan di Fakultas Ilmu Keolahragaan Universitas Negeri Jakarta dengan subjek penelitian sebanyak 20 orang guru SMA Penjasorkes se-Jakarta Timur. Dari hasil pengamatan yang dilakukan pada saat pelatihan berlangsung, para peserta pelatihan memiliki semangat dan motivasi besar dari awal hingga akhir pelatihan. Peserta juga sangat puas dengan adanya pelatihan seperti ini, dimana mereka dapat menambah pengetahuan, kemampuan serta keahlian dalam baris-berbaris yang sesuai dengan Peraturan Baris berbaris milik TNI/POLRI. Berdasarkan hasil penelitian dapat disimpulkan bahwa motivasi dan antusiasme peserta dalam mengikuti pelatihan baris-berbaris ini sangat baik dan tinggi. Terjadi interaksi positif antara tim pelaksana pelatihan dengan peserta pelatihan sehingga semua materi pelatihan dapat terserap sesuai dengan arahan dan standarnya. Pelatihan baris-berbaris untuk guru guru SMA penjasorkes se-Jakarta Timur ini sangat penting dilakukan agar dapat lebih meningkatkan pengetahuan, kemampuan dan keterampilan para guru sehingga mereka dapat memaksimalkan kemampuan dan keahlian dalam baris-berbaris.